Friction, Lubrication and Wear - Asaduzzaman Chowdhury, Mohammad (IntechOpen, 2019)
Tribology has rapidly expanded in recent years as the demand for improved materials has increased. The good function of numerous electrical, electrochemical, mechanical, and biological systems or components depends on suitable friction, lubrication, and wear as well as tribological values. In this context, the study of friction, wear, and lubrication is of tremendous pragmatic importance. The reduction of friction and loss of materials in relative motion are important challenges to improveing energy efficiency. This book guides the rational design of material for technological application. Chapters cover topics such as the resistance of dry abrasive wear, the role of a brand-new additive in the minimization of friction and wear, the structural-energy model of elastic-plastic deformation, the influence of micro-abrasive wear modes, tribological characteristics of magneto-rheological fluids (MRFs) and magneto-rheological elastomers (MREs), and different treatment technologies to improve tribological properties, among others.